Enhancing care for children with mental retardation through family support and motivation - saswati, nofrida; Harkomah, Isti; Pairi, Agus (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Mentally retarded children have limited intelligence and limitations in self-care abilities. So it takes support and motivation from the family. The research aims to explore the relationship between family support and motivation in caring for children with mental retardation. Methods: Cross Sectional Research Design. Held on 9-31 March 2021, population 180, sampling with the Total Sampling technique totaled 180 children with moderate mental retardation. Data was obtained by using a questionnaire. Data analysis was univariate and bivariate using Chi-Square test. Results: The results of the study mostly have good family support as many as 102 (56.66%) respondents, high motivation as many as 120 (66.66%) respondents and good care of mentally retarded children as many as 117 (65.00%) respondents. There is family support (p value = 0.045) and motivation (p value = 0.047) towards the treatment of mentally retarded children with p value <0.05. Conclusion: There is a relationship between family support and motivation with the treatment of mentally retarded children.